Changing Genres and Language Styles in Contemporary Chinese Lifestyle Magazines. Issue 1 (May 2013) - Chen, Ariel; Machin, David
The magazine market in China has been changing steadily as global media corporations have brought their international titles into China and as local Chinese titles have had to transform in order to meet the changing market and the arrival of advertising-driven content. This article analyses the changing visual styles, linguistic genres and language styles in the women's lifestyle magazine Rayli over the past ten years, showing how these increasingly seek to foster identities, ideas and values appropriate to a global culture ideology of consumerism.